A self-enhanced and recyclable catalytic system constructed from magnetic bi-nano-bionic enzymes for real-time control of RAFT polymerization. Issue 4 (17th December 2019) - Liu, Maosheng; Chen, Tao; Cai, Jintao; Zhang, Aitang; Liu, Ying; Yan, Guowen; Barrow, Colin J.; Yang, Wenrong; Xu, Jiangtao; Liu, Jingquan
Abstract : Flower-like Fe3 O4 @Au nanoparticles are constructed as bi-nano-bionic enzymes to catalyze the generation of hydroxyl radicals as an initiator for RAFT controlled polymerizations. Abstract : Environmentally harmful and high-priced initiators such as azodiisobutyronitrile, perchloric acid and butyllithium are usually essential for most of the polymerization technologies such as radical, cationic and anionic polymerizations. Besides, it is also troublesome to achieve complete separation of initiators from the obtained polymers. Herein, a recyclable catalytic system for the generation of hydroxyl radicals by catalyzing hydrogen peroxide based on bi-nano-bionic enzymes (refers to the bionic enzymes constructed from two kinds of enzymes, Fe3 O4 @Au NPs) was successfully constructed. The magnetic and flower-like Fe3 O4 NPs provided a recyclable and well-dispersed scaffold for immobilization of Au NPs, leading to enhanced catalytic activity of Au bionic enzymes. The designed catalytic system showed excellent catalytic activity for hydroxyl radical generation under various working conditions (pH 7–11, 15–100 °C). Impressively, the catalytic system was then employed as a novel initiating system (Fe3 O4 @Au NPs/H2 O2 ) for reversible addition–fragmentation chain transfer (RAFT) polymerization of a wide range of functional monomers using different RAFT agents in both aqueous and organic solvents. The established initiating system provided an effective method for RAFT polymerization with a real-time control feature in a recyclable way by magnetic separation. It was found that over 93.9% catalytic activity of Fe3 O4 @Au was still retained after 4 consecutive operations of RAFT polymerization.